Assessment of Aquifer Susceptibility due to Excessive Groundwater Abstraction; a Case Study of Yogyakarta-Sleman Groundwaer Basin - Putra, Doni Prakasa Eka (2014)
Yogyakarta-Sleman groundwater basin is one of productive groundwater basins in Indonesia. The groundwater basin is built by unconfined sand-aquifer system. Since the early 1980's many schools, universities and hotels have been developed in this area to support education and tourism activities, and since the beginning of 2000's the number of buildings has increased significantly.